PROFIL WORKER READINESS LULUSAN SMK DALAM KONTEKS INDUSTRI 4.0 - Ina Nurjanah, - (2022)
Worker Readiness graduates are a serious problem for vocational schools in the Industry 4.0. The researcher aims to identify Worker Readiness profiles of SMK graduates, find uniformity of Worker Readiness aspects, and identify the most priority Worker Readiness aspects needed by SMK graduates in the context of Industry 4.0. Beginning with a Systematic Literature Review of 90 journals, then a virtual Focus Group Discussion of 5 vocational teachers and 4 industry practitioners, followed by the distribution of google-form to 30 respondents who graduated from vocational schools. The findings of ten aspects of Worker Readiness are readiness for technology adoption, communication, collaboration, adaptation, problem solving analysis, critical thinking, innovation, independence, creativity, and curiosity. The results of the discussion processed with NVIVO found that graduates must have found that graduates must have the ability to adopt technology, adapt, curiosity, problem analysis ability, critical thinking ability and have an innovative creative spirit. Meanwhile, the results of the survey, which was processed using the Analytical Hierarchy Process, found that creative and innovative attitudes were the most priority aspects of Worker Readiness needed by SMK graduates in the context 4.0. The results of this study are expected to be information material for the government as policy makers, schools in improving the quality of graduates and teaching, industry in improving the quality of workers, as well as for students and graduates in preparing themselves to become workers who have work readiness in the Industry 4.0 era.